Шлях вищої освіти: проблема схвалення дівочого вибору російським суспільством (друга половина ХІХ - початок ХХ ст.) - Драч, О.О. (Наука. Релігія. Суспільство, 2009)
У статті аналізується відношення представників державної влади, широких кіл суспільства, родини та батьків
до нової стратегії жіночої поведінки, зорієнтованої на отримання вищої освіти. Окреслюється точка зору
дівчат того часу, які навчаються, на проблему особистого життєвого вибору. В статье анализируется отношение представителей государственной власти, широких слоев общества, семей
и родителей к новой стратегии женского поведения, ориентированной на получение высшего образования.
Выявляется точка зрения учащихся девушек того времени на проблему собственного жизненного выбора. The main theme of the article is the issue of social reaction to the women’s desire to get higher education in the context
of evolutional changes of the social position of the weaker sex during the period of modernization in the second
half of the XIX-th and at the beginning of the XX-th century. The government has accepted the decision to make
it easier for women to get higher education. But there were many dissatisfactions in this prospect which denied women’s
ability and desire to enter higher institutions.